2014
DOI: 10.1002/jrs.4594
|View full text |Cite
|
Sign up to set email alerts
|

Multiple weak interaction‐assisted SERS detection platform for triadimefon

Abstract: In this paper, a surface enhanced Raman spectra (SERS) detection platform for the widely used pesticide of triadimefon (TDF) is described. TDF is difficult to connect to the gold/silver SERS substrate, but the optical properties of the probe molecule 4-mercaptobenzoic acid (4-MBA), including the peak intensity and the peak position, are easily altered by the multiple weak interaction-assisted SERS detection platform. The limit of detection (LOD) of this method is 1.0 × 10 -9 M, and the linear range is from 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These approaches provide high selectivity but restricted by the structure of target. Meanwhile, intermolecular interactions, such as hydrogen bond, van der Waals interaction force, hydrophilicity, and so forth are also utilized to improve the highly sensitive selectivity. For example, by manipulating the size distribution of aggregates and trapping interest analyte into hotspot region by electrostatic interaction between halide ion, target, and Au NPs, the qualitative analysis of opioids with high sensitivity was achieved .…”
Section: Introductionmentioning
confidence: 99%
“…These approaches provide high selectivity but restricted by the structure of target. Meanwhile, intermolecular interactions, such as hydrogen bond, van der Waals interaction force, hydrophilicity, and so forth are also utilized to improve the highly sensitive selectivity. For example, by manipulating the size distribution of aggregates and trapping interest analyte into hotspot region by electrostatic interaction between halide ion, target, and Au NPs, the qualitative analysis of opioids with high sensitivity was achieved .…”
Section: Introductionmentioning
confidence: 99%
“…TEM characterization of alectinib is shown in Figure a, and in Figure b, the size of the gold nanoparticles is 36 ± 6 nm. UV–vis absorption spectrum can be used to determine the morphology, size, and aggregation state of gold nanoparticles in solution and has been applied to the study of surface adsorption and other fields. , Figure c shows the UV–vis absorption spectra of AuNP solution and the mixed solution of alectinib and AuNPs. The UV–vis absorption spectrum (red curve) of AuNP solution has a strong absorption peak at a wavelength of 526 nm, which is the characteristic peak of the surface plasmon resonance band of AuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…described a SERS detection platform for the widely used pesticide of triadimefon (TDF). They found that TDF interacts directly with the carboxyl of the probe molecule and consequently has an effect on the ring vibrations . Ramos‐Berdullas and co‐workers described the mechanism responsible for Raman enhancement on carbon allotropes surfaces and the role of molecule‐surface vibrational coupling in SERS.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%